2018
DOI: 10.1111/eva.12673
|View full text |Cite
|
Sign up to set email alerts
|

Broad thermal tolerance is negatively correlated with virulence in an opportunistic bacterial pathogen

Abstract: Predicting the effects of global increase in temperatures on disease virulence is challenging, especially for environmental opportunistic bacteria, because pathogen fitness may be differentially affected by temperature within and outside host environment. So far, there is very little empirical evidence on the connections between optimal temperature range and virulence in environmentally growing pathogens. Here, we explored whether the virulence of an environmentally growing opportunistic fish pathogen, Flavoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…As our results are based from experimental infections, further validation from field observations is required to reduce uncertainty. Whether or not higher temperatures select for increased pathogen virulence is still under discussion 21,45 ; yet, extreme thermal increases are known to cause stress and compromise immune systems in most aquatic species, making them more vulnerable to infections 46,47 . Previous research found, for example, that an increase in severe disease outbreaks in aquatic species at lower latitudes could be partly due to warmer temperatures and higher nutrient contents 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As our results are based from experimental infections, further validation from field observations is required to reduce uncertainty. Whether or not higher temperatures select for increased pathogen virulence is still under discussion 21,45 ; yet, extreme thermal increases are known to cause stress and compromise immune systems in most aquatic species, making them more vulnerable to infections 46,47 . Previous research found, for example, that an increase in severe disease outbreaks in aquatic species at lower latitudes could be partly due to warmer temperatures and higher nutrient contents 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that S. chromogenes adapted better to high culturing temperatures at 42˚C than at 37˚C (Figs 3B and S7B). Previous reports indicate that tolerance to high temperatures is highly related to bacterial virulence for better investments in resource acquisition and other purposes [47,48]. In contrast to those in bovine-originating S. chromogenes [29,49], the diversity of virulence genes in bird-derived isolates is much lower (S5 Fig) . The compromise of the survival of S. chromogenes may attenuate its pathogenicity to hosts, which is consistent with our observation that clinical symptoms were barely recognized after birds were infected solely with S. chromogenes (S9 Fig) . Notably, temperature adaptability may explain its irreplaceable role in infections of the avian respiratory tract due to intrinsically high body temperatures ranging from 40 to 43˚C.…”
Section: Discussionmentioning
confidence: 91%
“…chromogenes adapted better to high culturing temperatures at 42°C than at 37°C (Figs 3B and S7B ). Previous reports indicate that tolerance to high temperatures is highly related to bacterial virulence for better investments in resource acquisition and other purposes [ 47 , 48 ]. In contrast to those in bovine-originating S .…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have tested how different species or populations differ in their thermal performance curves, or if evolution has been able to shape them (e.g. Krenek et al ., 2011; Ketola and Saarinen, 2015; Ashrafi et al ., 2018; Maclean et al ., 2019), only a few studies have determined the evolutionary potential of thermal performance curves. In these studies, the genetic variance-covariance matrix (G-matrix) for thermal performance across several temperatures has been estimated, and how genetic variation is aligned with characteristic directions of reaction norm evolution has been determined (e.g.…”
Section: Introductionmentioning
confidence: 99%